Cruciforms’ polarized emission confirms disjoint molecular orbitals and excited states - Gard, Matthew N.; Dreuw, Andreas; Bunz, Uwe H. F. (Organic letters, 2012)
Steady-state and time-resolved polarized spectroscopy studies reveal that electronic excitation to the third excited state of 1,4-distyryl-2,5-bis(arylethynyl)benzene cruciforms results in fluorescence emission that is shifted an angle of ca. 60°. This result is consistent with quantum chemical calculations of the lowest electronic excited states and their transition dipole moments. The shift originates from the disjointed nature of the occupied molecular orbitals being localized on the different branches of the cruciforms.
Gesehen am 18.12.2017